Peran Wali Kelas Dalam Meningkatkan Minat Belajar Peserta Didik Di SDN 17 Pekanbaru - Laminah, Laminah (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
Education is a necessity for human life because No one was born by knowledge. The schools as institutions are trusted by the community and responsible to conduct education. The school responsibility would not succeed without teachers ‘roles. The form teacher is the has the first opportunity to improve the students' interest through their role in teaching, guiding and preparing students psychologically, participate in and carry out learning activities. So the quality of the process and learning outcomes could be achieved. The purpose of this study was to determine the role of the homeroom teacher in increasing the learning interest at students of SDN (State Elementary School) 17 Pekanbaru. The research was descriptive qualitative research. The research subjects were 4 form teachers, principals, 19 students, and the parents. Data collection techniques were observation, interviews and documentation. Then the data was analysed through the data reduction, data presentation, and drawing conclusions. The results of this study indicated that the role of the form teacher in improving students' interest in learning well according to the abilities of the form teacher and needs to be improved more. To ensure the achievement the achieve the goals. The role of the form teacher to improve students’ interest in learning is also evaluated by the school principal, the principal always provides supervision of improvements further improvement in the learning process. Held the meetings or meetings with the form teacher twice in one semester to evaluate the duties and responsibilities as a teacher